2022
DOI: 10.3389/fmicb.2022.822864
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Characterization of an Oxidative Stress-Resistant Saccharomyces cerevisiae Strain Obtained by Evolutionary Engineering

Abstract: Oxidative stress is a major stress type observed in yeast bioprocesses, resulting in a decrease in yeast growth, viability, and productivity. Thus, robust yeast strains with increased resistance to oxidative stress are in highly demand by the industry. In addition, oxidative stress is also associated with aging and age-related complex conditions such as cancer and neurodegenerative diseases. Saccharomyces cerevisiae, as a model eukaryote, has been used to study these complex eukaryotic processes. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…Recent findings with yeast cells that are resistant to diverse metals and oxidative stress showed that silver-resistant, iron-resistant, nickel-resistant, and oxidative stress-resistant yeasts had upregulated and mutated genes related to cell wall integrity and organization. Their cell wall integrity test results also revealed that they had increased cell wall integrity levels, indicating the importance of cell wall in stress resistance [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings with yeast cells that are resistant to diverse metals and oxidative stress showed that silver-resistant, iron-resistant, nickel-resistant, and oxidative stress-resistant yeasts had upregulated and mutated genes related to cell wall integrity and organization. Their cell wall integrity test results also revealed that they had increased cell wall integrity levels, indicating the importance of cell wall in stress resistance [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the glycogen content of both strains was not significantly different from each other both in the absence and presence of 2-PE ( Supplementary Figure S4 ). In previous studies dedicated to evolve yeasts to become resistant to either caffeine ( Sürmeli et al, 2019 ), iron ( Balaban et al, 2020 ), silver ( Terzioğlu et al, 2020 ), or oxidative stress ( Kocaefe-Özşen et al, 2022 ), we reported a relationship between resistance to these stresses and cell wall remodeling. Therefore, we also examined whether the resistance to 2-PE entailed some cell wall remodeling by a treatment of the strains with lyticase, a cell wall-degrading enzymatic cocktail ( Kuranda et al, 2006 ).…”
Section: Resultsmentioning
confidence: 84%
“…Lyticase sensitivity assay was performed according to Kuranda et al (2006) with slight modifications, as described previously ( Kocaefe-Özşen et al, 2022 ). Briefly, overnight cultures of the evolved and the reference strain, grown both in the presence and absence (control) of 3 g/L 2-PE stress were harvested upon centrifugation at 10,000 g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Orthologs of some genes regulated by Euf1 were also involved in adaptation to diverse stress conditions. In S. cerevisiae CIT1 and MLS1 were upregulated in strains adapted to oxidative stress [ 49 ], and upregulation of genes encoding alcohol and aldehyde dehydrogenases were observed in strains resistant to 2-Phenylethanol [ 50 ].…”
Section: Discussionmentioning
confidence: 99%